Cardiac baroreceptor sensitivity: a prognostic marker in predialysis chronic kidney disease patients? (2005)
Background. Small, uncontrolled studies of dialysis dependent chronic kidney disease (CKD) patients have demonstrated abnormalities of cardiovascular autonomic control and vascular compliance, which may contribute to adverse cardiovascular morbidity in this population. However, there is little information utilizing newer, noninvasive techniques in predialysis patients with increasing degrees of uremia. Methods. One hundred and five nondialysis CKD patients with a median GFR of 23 mL/min/1.73m2 (range: 6 to 102) at baseline were studied. Cardiac baroreceptor sensitivity (BRS) was recorded by time- and frequency-domain techniques, and its relationship with increasing degrees of uremia studied. During a mean follow-up period of 42 months (range: 3 to 70), primary (death, dialysis, transplantation) and secondary (fatal and nonfatal cardiovascular events) outcome measures were recorded. The importance of cardiac BRS in comparison to other important renal and cardiovascular prognostic variables in predicting outcome was assessed. Results. Median cardiac BRS by time domain analysis at baseline was 8.85 msec/mm Hg (interquartile range: 6.85), and impaired cardiac BRS was related to reduced GFR, increasing age, and hypertension on quantile regression analysis. ‘Impaired’ cardiac BRS was associated with a trend toward increased likelihood of both primary and secondary outcomes, and may act as a surrogate measure of other cardiovascular risk factors, including age, hyperlipidemia, hypertension, previous cardiovascular disease, and doubling of creatinine. Conclusion. Nondialysis-dependent CKD patients have impaired cardiac BRS, and this was related to decreasing GFR. There was a trend toward poorer prognosis in patients with impaired cardiac BRS that requires further study. Cardiac BRS may provide a simple, bedside, noninvasive assessment of overall cardiovascular risk in this population.